Factors Associated with Anxiety and Depressive Symptoms in 2775 Patients with Arterial Hypertension and Coronary Heart Disease: Results from the COMETA Multicenter Study. Issue 1 (19th October 2021) - Pogosova, Nana; Boytsov, Sergey; De Bacquer, Dirk; Sokolova, Olga; Ausheva, Aza; Kursakov, Alexander; Saner, Hugo
Aim: To identify associations of anxiety symptoms (AS) and depressive symptoms (DS) with other psychosocial and lifestyle risk factors in primary care patients with arterial hypertension (AH) and/or coronary heart disease (CHD). Methods: COMETA (Clinical-epidemiOlogical prograM of studying psychosocial risk factors in cardiological practice in patiEnts with arterial hyperTension and ischemic heArt disease) is a multicenter cross-sectional study performed in 30 big cities of Russia with two to five out-patient clinics per city randomly selected and two to five general practitioners (GPs) per an out-patient clinic. Each GP included 8–10 consecutive patients with AH and/or CHD. AS and DS were assessed by the Hospital Anxiety and Depression Scale. Results: 325 GPs enrolled 2775 patients (mean age 66.7 years, 72% women) with AH (60.8%), CHD (2.6%), and AH plus CHD (36.6%). Moderate/severe (≥11 HADS) AS were found in 25.5% and DS in 16.3% patients. The strongest associations of AS and DS were revealed for high stress level (OR 5.79; 95% CI [4.18–8.03]), moderate stress level (OR 2.34; 95% CI [1.73–3.16]), low social support (OR 1.87; 95% CI [1.31–2.68]) and female gender (OR 1.78; 95% CI [1.41–2.25]). Low physical activity, unhealthy eating, unemployment and low income were also positively associated with both AS and DS (p < 0.003 for all). Conclusion: In out-patients with AH and CHD, AS and DS were strongly associated with higher levels of stress, low social support, unemployment, low family income and unhealthy lifestyle such as low physical activity, low fruit and vegetables intake and excessive salt consumption. Our findings indicate that patients with AH and CHD, who have anxiety and depressive symptoms need extra attention and monitoring in regard to stress and lifestyle risk factor control.